Application of the Six-Step Standard Communication Process in the Communication Training for Newly Recruited Nurses in Cancer Specialist Hospitals - Geng, Jingzhi; Liu, Miao; Zhang, Huanhuan; Gao, Jian; Wang, Li; Zhang, Yu; Ma, Fengyan; Liu, Yan (Frontiers in Surgery, 2022)
Abstract Purpose: Discuss the application effect of the six-step standard communication process in the communication ability training of newly recruited nurses. Methods: This is a before and after control study. The control group included 45 newly recruited nurses in our hospital in 2019, and the observation group included 40 newly recruited nurses in our hospital in 2020. The control group completed the training according to the existing communication training program, and the observation group implemented a training program based on the “six-step standard communication process” on the basis of the existing communication training. The training period was 12 months. The training effect of the two groups of new nurses was compared. Results: After training, the total scores of clinical communication skills of the new nurses in the control group and observation group were 252.56±24.950 and 268.05±19.335 points respectively ; the total scores of communication behavior were 39.00±4.676 and 48.08±2.515 points respectively; the total scores of general self-efficacy were 26.89±3.017 and 31.25±5.027 points respectively; the satisfaction scores of communication training were 17.56±2.018 and 19.45±0.986 points respectively, and the differences were statistically significant (P<0.05). Conclusion: The implementation of a training program based on the "six-step standard communication process" can effectively improve the clinical communication skills and self-efficacy of newly recruited nurses, and can be promoted and applied to the communication training of newly recruited nurses.